Connecting Corporate Social Responsibility (CSR) to Customer Loyalty: A Mediation Analysis in Hoteling Industry of Pakistan. (December 2021) - Shah, Muhammad Usman; Jan, Muhammad Farooq
This study examines the role of Corporate Social Responsibility (CSR) in enhancing customer loyalty by exploring direct and mediating effects of trust, credibility, and word of mouth. Cross-sectional data of 463 respondents was taken from Pakistan using an online survey because of the limitations of covid19. Hypotheses were tested using SmartPLS-3. Findings of the study revealed that CSR has affected customer loyalty significantly and positively. The mediating role of trust was found insignificant. Credibility and word of mouth were found as significant mediating variables in the linkage between CSR and Customer Loyalty. This study has provided a direction for the hoteling industry to incorporate CSR activities in their operation for gaining customer loyalty using empirical analysis. In this regard, this paper makes a significant contribution to the existing literature regarding the connections between CSR and customer loyalty with the help of trust, credibility, and word of mouth as mediators, which are not tested empirically in the existing literature.